Eksplorasi Motivasi Minat Mahasiswa Akuntansi Berinvestasi Di Pasar Modal - Fauziah, Putri (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This study aims to determine the influence of capital market socialization, capital market knowledge, and capital market learning motivation on accounting students' interest in capital market investment. This research focuses on how capital market socialization, learning motivation, and knowledge affect students' interest in investing in the capital market. To explore experiences, viewpoints, and social dynamics that can influence students' investment decisions, this study uses a qualitative type of research. The results of in-depth interviews with 25 accounting students with capital market investment experience show that information about capital markets comes from formal and informal sources, including peers, family, and personal experience. Students' interest in investing is significantly shaped by their learning motivation, both internal and external. In addition, the development of investment interest is significantly influenced by social interaction and shared experience in studying the capital market through campus socialization activities. The results of this study provide a better understanding of the psychosocial determinants of accounting students' interest in capital market investments. These findings have practical consequences that could guide the creation of more relevant academic curriculum and capital market socialization initiatives on campus. In addition, this study adds knowledge about student investment behavior and the advancement of financial literacy in the younger generation.